Effect of mycobacterium on clinical and laboratory parameters in COVID-19 - Shah, Vitrag; Patel, Pratik; Soni, Ameet (International Journal of Research in Medical Sciences, 2023)
Background: Initial wave of COVID-19 created a massive health crisis everywhere including India due to a limited understanding of the disease pathology. Most physicians used sepsis as a prototype to manage COVID-19, as there are similarities. Heat-killed Mycobacterium w (Mw) (inj. sepsivac®) is a known immunomodulator approved for the treatment of gram-negative sepsis. Our purpose of this observation is to evaluate the safety and efficacy of Inj sepsivac in COVID-19 patients along with the standard of care. Methods: Total 49 patients data with reverse transcriptase-polymerase chain reaction (RT-PCR) confirmed critically ill COVID-19 patients who were admitted at Velocity Hospital, Surat between May 4, 2021, and May 18, 2021 were evaluated. They were evaluated for vital parameters like pulse, blood pressure, respiratory rate and temperature as well as laboratory parameters like ALT, S IL-6, serum creatinine and CRP during three follow-up visits after the administration of Inj sepsivac. Further follow-up was done until the discharge/death of the patient. Results: There was a statistically significant reduction of mean CRP observed compared to the baseline value during all follow-up visits. The rest of the laboratory parameters as well as clinical assessment did not show any significant change as compared to baseline. Out of 49, two patients died (mortality rate; 4%). Inj. sepsivac was found to be well tolerated without any systemic side effects. Conclusions: The addition of Mw to the standard of care can improve laboratory parameters like CRP, without any safety concerns. These results should be further substantiated by larger randomised clinical trials.